How do bats see in the dark? : questions and answers about night creatures - Berger, Melvin; Berger, Gilda; Effler, James M. (New York, NY : Scholastic, 2000)
Questions and answers present the habitats and behavior of a variety of nocturnal animals, from cats and kiwis to bats, owls, and foxes.
Keywords: Nocturnal animals; Nocturnal animals; Questions and answers